1981
DOI: 10.1029/jb086ib06p04949
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform seismic slip rates along the Middle America Trench

Abstract: Revised estimates of seismic slip rates along the Middle America Trench are lower on the average than plate convergence rates but match them locally (for example, Oaxaca). Along the Cocos‐North American plate boundary this can be explained by nonuniformities in slip at points of aseismic ridge or fracture zone subduction. For at least 81 yr (and possibly several hundred years), no major (Ms ≥ 7.5) shallow earthquake is known to have occurred near the Orozco Fracture Zone and Tehuantepec Ridge areas. Compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(42 citation statements)
references
References 30 publications
(20 reference statements)
4
38
0
Order By: Relevance
“…If the modern rate of SSEs has been constant since the last earthquake in 1950, the summed moment for all of the SSEs over this period (2 × 10 21 Nm) is nearly an order of magnitude higher than the moment released by the 2012 earthquake (3.5 × 10 20 Nm) and is equivalent to a M w 8.2 earthquake. SSEs thus appear to be releasing 80-90% of the slip associated with relative plate motion, consistent with the historically low seismic coupling coefficient for this margin (27)(28)(29). We suggest that Central America tends to have smaller earthquakes compared with many other subduction zones because a significant fraction of slip occurs via frequent SSEs.…”
Section: Resultsmentioning
confidence: 56%
“…If the modern rate of SSEs has been constant since the last earthquake in 1950, the summed moment for all of the SSEs over this period (2 × 10 21 Nm) is nearly an order of magnitude higher than the moment released by the 2012 earthquake (3.5 × 10 20 Nm) and is equivalent to a M w 8.2 earthquake. SSEs thus appear to be releasing 80-90% of the slip associated with relative plate motion, consistent with the historically low seismic coupling coefficient for this margin (27)(28)(29). We suggest that Central America tends to have smaller earthquakes compared with many other subduction zones because a significant fraction of slip occurs via frequent SSEs.…”
Section: Resultsmentioning
confidence: 56%
“…The main shock was located at 15.77°N, 96.80°W McNally and Minster, 1981] at a depth of 18 km [Stewart et al, 1981]. Local seismic observations with portable field seismographs showed that the aftershocks were distributed over an area of $80 km (in the E-W direction) Â 65 km (in the N-S direction) and that their hypocenters had increasing depths inland from the trench [Singh et al, 1980], as shown in Figure 2.…”
Section: Rupture Processes Of the 1978 And 1999 Oaxaca Earthquakesmentioning
confidence: 99%
“…0094-8276/86/006L-6080$03.00 569 in 1941 and 1973 (a 32 yr interval), and to the southeast, the Petatlan area in northern Guerrero had events in 1943 and 1979 (a 36 yr interval). An average recurrence interval for the plate boundary of 33 ± 8 yrs was found by McNally and Minster [ 1981 ), although different sub-segments have somewhat different intervals [Astiz and Kanamori, 1984 l. South of the Petatlan zone in the middle of the coast, the area void of recent large earthquake activity is the Guerrero seismic gap. The distance from Mexico City to the Guerrero gap is shorter than to any other region along the Mid-America trench.…”
Section: Introductionmentioning
confidence: 99%
“…Previous to the September 1985 earthquake, the Michoacan area, with its seismic quiescence and subducting fracture zone, was similar to the southern Oaxaca area, where the Tehuantepec Ridge is subducting, and where there are no large earthquakes in the historic record. One possibility suggested to explain the seismic quiescence in these areas was that features such as the Orozco fracture zone and the Tehuantepec Ridge may be locally affecting the subduction process, such that the area is subducting aseismically, or more slowly than adjacent regions of the plate boundary [Singh et al, 1980;McNally and Minster, 1981;Lefevre and McNally, 1985). Alterations of subdue- [Singh et al, 19851.…”
Section: Introductionmentioning
confidence: 99%